Feeding and eating difficulties in early childhood – Characterization of a child psychiatry consultation - Carvalho e Marques, Pedro; Monteiro, Maria do Rosário; Rodrigues, Márcia; Fernandes, Graça; Martins, Vânia (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
Introduction: Feeding difficulties in early childhood are among the most common problems reported by parents and may reflect the child’s own characteristics or a relational problem. They are associated with problems in later life, such as behavioral disorders, cognitive deficits, and eating disorders. Materials and Methods: This study was a retrospective, descriptive analysis of sociodemographic and clinical data of children under six years of age with feeding or eating problems evaluated at a first consultation in a child psychiatry unit of a tertiary hospital between January 2019 and May 2021. Children with a diagnosis or suspected diagnosis of autism spectrum disorder were excluded. Results: Of a total of 647 children evaluated, 57 (8.81%) were classified as having feeding difficulties. Their median age was 24.5 months. Food selectivity was the most frequently reported problem (45.6%), followed by difficulties in self-regulation at mealtimes (43.9%) and decreased appetite (33.3%). Among the mothers, 21% had a history of depressive disorders and 7% had a history of anxiety disorders. Forty-nine percent of children had patterns of interaction with their primary caregiver that were considered worrisome or disruptive. Fifty-four percent of the therapeutic interventions provided were child-parent psychotherapy. Conclusions: Early identification and intervention are needed for children with feeding problems. Feeding problems are common in early childhood and a multidisciplinary approach must always be considered as they can affect several domains of the child’s health and development.